Alteration of hair growth in mice by circulating exosomes from Xinji fine-wool and small-tailed Han sheep - Zhang, Xinyu; Wang, Wei; Fan, Wei; Zhai, Yilu; Fu, Jiaqi; Cai, Jinshun; Zhao, Dazhuo; Sun, Fuliang (Frontiers in Animal Science, 2025)
IntroductionAnimal hair growth is an important research topic in the field of breeding. Hair growth is affected by circulating exosomes in the plasma, and sheep wool fiber thickness is altered by intravenous injection of miRNA mimics.MethodsThis study investigated the effect of miRNAs in circulating exosomes on an animal’s hair growth. Circulating exosomes were isolated from Xinji fine-wool and small-tailed Han sheep plasma using a two-phase system. A blank control group (NC), groups of model mice injected with exosomes from Xinji fine-wool sheep (XPE), and groups of model mice injected with exosomes from small-tailed Han sheep group (SPE) were set up as three groups of hair regeneration models.ResultsThe results showed that the diameter of hair follicles in the XPE group was significantly smaller than that of the NC and SPE groups (P < 0.05), and the diameter of hair follicles in the SPE group was significantly larger than that of the NC and XPE groups (P < 0.05). There was no significant difference in the number of hair follicles among the three groups directly (P > 0.05). The diameter of hairs in the SPE group was highly significantly greater than that in the NC and XPE groups (P < 0.001), and the diameter of hairs in the XPE group was significantly greater than that in the NC and SPE groups (P < 0.01). In addition, the expression of the hair follicle growth markers Lef1, Wnt10b, Dkk1, b-catenin, Ptch1, and Shh indicated that circulating exosomes can accelerate the hair follicle development cycle. The expression of the hair melanin synthesis genes FZD3 and FZD4 indicated that circulating exosomes can affect hair follicle melanin synthesis. Immunohistochemistry results showed that the SPE group had greater levels of a-SMA protein. miR-31-5p, miR-133b, miR-433-3p, and miR-218 were similarly expressed in different samples, and the expression of all these miRNAs was significantly greater in the SPE group compared with the XPE group (P < 0.05). Circulating exosomes in Xinji fine-wool and small-tailed Han sheep altered the hair growth in mice.